2017
DOI: 10.1140/epjc/s10052-017-5322-7
|View full text |Cite
|
Sign up to set email alerts
|

Analytical study of anisotropic compact star models

Abstract: A simple classification is given of the anisotropic relativistic star models, resembling the one of charged isotropic solutions. On the ground of this database, and taking into account the conditions for physically realistic star models, a method is proposed for generating all such solutions. It is based on the energy density and the radial pressure as seeding functions. Numerous relations between the realistic conditions are found and the need for a graphic proof is reduced just to one pair of inequalities. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 112 publications
3
92
0
1
Order By: Relevance
“…more recently this equivalence between the restriction on pressures and velocities was demonstrated in [16] and included as part of the acceptability conditions that have to be considered when building physically reasonable compact object models. We shall discuss these constraints in the next section.…”
Section: Convection and Cracking Sources Of Instabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…more recently this equivalence between the restriction on pressures and velocities was demonstrated in [16] and included as part of the acceptability conditions that have to be considered when building physically reasonable compact object models. We shall discuss these constraints in the next section.…”
Section: Convection and Cracking Sources Of Instabilitymentioning
confidence: 99%
“…Additionally B.V Ivanov [16], demonstrated that these conditions are not independent and can be condensed in five main inequalities:…”
Section: Physical Acceptability Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature y is given and a 1 is found from Eq (32) [30], [31], [32], [33], [34], [35], [36], [37], [38], [39]. Due to Eqs (6, 7) one finds quickly y form µ or m. Solutions with LEOS and known µ are given in [40], [41], [42] and [43].…”
Section: Types Of Equationsmentioning
confidence: 99%
“…where ǫ denotes the total-energy density, p the radial pressure, and c s the radial sound speed, respectively [40].…”
Section: The Conservation Of Baryon Numbermentioning
confidence: 99%